ORAI1 Mutations with Distinct Channel Gating Defects in Tubular Aggregate Myopathy. Issue 4 (2nd February 2017) - Böhm, Johann; Bulla, Monica; Urquhart, Jill E.; Malfatti, Edoardo; Williams, Simon G.; O'Sullivan, James; Szlauer, Anastazja; Koch, Catherine; Baranello, Giovanni; Mora, Marina; Ripolone, Michela; Violano, Raffaella; et al.
Abstract : Tubular aggregate myopathy (TAM) is a progressive muscle disorder typically showing densely packed membrane tubules on biopsies. We identified mutations in the Ca 2+ channel ORAI1 as the genetic cause of TAM, and we uncovered a mutation‐dependent pathomechanism. Mutations in the pore‐forming domain generate a constantly permeable ORAI1 channel, while a mutation in the concentric channel ring alters the channel permeability only in the presence of the Ca 2+ sensor STIM1, and is therefore associated with a milder phenotype. ABSTRACT: Calcium (Ca 2+ ) is a physiological key factor, and the precise modulation of free cytosolic Ca 2+ levels regulates multiple cellular functions. Store‐operated Ca 2+ entry (SOCE) is a major mechanism controlling Ca 2+ homeostasis, and is mediated by the concerted activity of the Ca 2+ sensor STIM1 and the Ca 2+ channel ORAI1. Dominant gain‐of‐function mutations in STIM1 or ORAI1 cause tubular aggregate myopathy (TAM) or Stormorken syndrome, whereas recessive loss‐of‐function mutations are associated with immunodeficiency. Here, we report the identification and functional characterization of novel ORAI1 mutations in TAM patients. We assess basal activity and SOCE of the mutant ORAI1 channels, and we demonstrate that the G98S and V107M mutations generate constitutively permeable ORAI1 channels, whereas T184M alters the channel permeability only in the presence of STIM1. These data indicate a mutation‐dependent pathomechanism and a genotype/phenotype correlation, as the ORAI1 mutations associated with the most severe symptoms induce the strongest functional cellular effect. Examination of the non‐muscle features of our patients strongly suggests that TAM and Stormorken syndrome are spectra of the same disease. Overall, our results emphasize the importance of SOCE in skeletal muscle physiology, and provide new insights in the pathomechanisms involving aberrant Ca 2+ homeostasis and leading to muscle dysfunction.